2014
DOI: 10.3389/fevo.2014.00045
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide to identifying members of the Bemisia tabaci species complex: and other morphologically identical species

Abstract: Members of the Bemisia tabaci species complex (whiteflies) are a considerable threat to a broad range of agriculture and horticulture food and fiber crops. There are hundreds of papers a year published on the members of B. tabaci species complex, many failing to either correctly identify the species involved or confusing identity. Correct identification is a crucial first step in any study, yet all too often, especially in cases where the primary focus of the study is plant pathology, is overlooked. The whitef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 42 publications
(51 reference statements)
0
81
0
2
Order By: Relevance
“…1,2 One of the cryptic species, Middle East Asia Minor 1 (MEAM1, previously referred to as the B "biotype") has invaded many regions of the world and caused extensive crop damage through direct feeding and transmission of plant viruses. 3,4 More than 200 species of plant viruses are exclusively transmitted by the whitefly B. tabaci, mostly begomoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 One of the cryptic species, Middle East Asia Minor 1 (MEAM1, previously referred to as the B "biotype") has invaded many regions of the world and caused extensive crop damage through direct feeding and transmission of plant viruses. 3,4 More than 200 species of plant viruses are exclusively transmitted by the whitefly B. tabaci, mostly begomoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported new species (Asia II 9, Asia II 10, Asia III, and China 3, and Asia I-India and New World 2), for a total number of 34 morphologically [24] indistinguishable species reported in the B. tabaci complex [25,26,27]. The worldwide spread of emerging species, such as B. tabaci MEAM1, also known as B. argentifolii , and a Bemisia tabaci MED, continue to cause severe crop losses which will likely continue to increase, resulting in higher pesticide use on many crops (tomato, beans, cassava, cotton, cucurbits, potato, sweet potato).…”
Section: Introductionmentioning
confidence: 99%
“…PCR products were analyzed on agarose gels and at least one PCR amplicon per sampling location was sequenced (Sequiserve, Vaterstetten, Germany). Partial mtCOI sequences were trimmed to 657 bp (Dinsdale et al 2010) and analyzed using the Global Bemisia dataset release version 31 (De Barro and Boykin 2013;Boykin and De Barro 2014) for species identification. Sequences were aligned using ClustalW v1.8 (Thompson et al 1994).…”
Section: Analysis Of Bemisia Tabaci Cryptic Speciesmentioning
confidence: 99%
“…3.2; (Ronquist et al 2012) following the method described by Dinsdale et al (2010). Sequences of this study were assigned to species (Dinsdale et al 2010) and named according to Boykin and De Barro (2014) with modifications. The format is: Species_Country [In = India]_Year of sampling_Location_Host.…”
Section: Analysis Of Bemisia Tabaci Cryptic Speciesmentioning
confidence: 99%
See 1 more Smart Citation